2021
DOI: 10.3390/s21113886
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Gas Sensor Based on Graphene Oxide-Coated Mach-Zehnder Interferometer with Hybrid Fiber Structure

Abstract: A graphene oxide-coated in-fiber Mach-Zehnder interferometer (MZI) formed with a multimode fiber-thin core fiber-multimode fiber (MMF-TCF-MMF) is proposed and experimentally demonstrated for ammonia gas (NH3) sensing. The MZI structure is composed of two segments of MMF of length 2 mm, with a flame-tapered TCF between them as the sensing arm. The MMFs act as mode couplers to split and recombine light owing to the core diameter mismatch with the other fibers. A tapered TCF is formed by the flame melting taper m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Fe 2 O 3 -coated tapered microfiber interferometer (MFI) [ 14 ] has a very wide detection range, but its sensitivity is correspondingly low. The GO-coated MZI sensor [ 15 ] also presents a wide detection range; however, its response time is too long to limit its practical application. The graphene-coated MZI sensor [ 17 ] is made of a pair of 3 dB LPFGs, which achieved good response in the NH 3 concentration range of 10–180 ppm, while its response time is also long, and its fabrication is very complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fe 2 O 3 -coated tapered microfiber interferometer (MFI) [ 14 ] has a very wide detection range, but its sensitivity is correspondingly low. The GO-coated MZI sensor [ 15 ] also presents a wide detection range; however, its response time is too long to limit its practical application. The graphene-coated MZI sensor [ 17 ] is made of a pair of 3 dB LPFGs, which achieved good response in the NH 3 concentration range of 10–180 ppm, while its response time is also long, and its fabrication is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…The Fe 2 O 3 nanotubes were used as the sensitive layer to enhance the adsorption of NH 3 molecules and the intensity distribution of the evanescent field of the sensor, achieving an extreme range of NH 3 detection. Fan et al [ 15 ] proposed an NH 3 sensor based on the Mach–Zehnder interferometer (MZI). A linear response to NH 3 in the range of 0–151 ppm was achieved by coating the sensor surface with graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, incorporation of sol-gel silica which exhibit porous structures can attribute to better adsorption of analyte molecules. Due to the presence of multiple functional groups such as Si-O-Si and Si-OH, the realization of sol-gel silica is ideal solution to capture the small molecules such as CH 4 by forming the surface hydrogen bonds [15]. As the methane molecules present, the adsorption of methane with the silica nanostructure at the cladding-air interface took place via physisorption which subsequently affect the hole concentration of silica.…”
Section: Sensor Structure and Principlementioning
confidence: 99%
“…Therefore, PDIs are promising materials for the development of optical sensors for ammonia detection. In recent years, several authors presented high sensitivity ammonia sensors based on functionalized optical fibers applied to detect ammonia in gas phase and liquid solution [12][13][14][15][16][17] A recent review of fiber optic sensors for gases, vapors and ions can be found at [18]. Fiber Bragg gratings are a class of optical sensors that have attracted attention of researchers in recent decades due to properties such as wavelength coding, multipoint remote sensing, electrical passivity and electromagnetic immunity.…”
Section: Introductionmentioning
confidence: 99%